2009
DOI: 10.1590/s0100-39842009000600010
|View full text |Cite
|
Sign up to set email alerts
|

Tumores glômicos subungueais: achados de imagem

Abstract: OBJECTIVE: To evaluate main imaging findings of subungual glomus tumors. MATERIALS AND METHODS: Retrospective study of eight cases of subungual glomus tumors from the archives of two private clinics in Goiânia, GO, Brazil. Plain radiographs were obtained in five cases, Doppler ultrasonography in five, and magnetic resonance imaging in five cases. RESULTS: Mean age of the patients included in the present study was 39 years, with female predominance (7:1). Tumors didn't present prevalence in any specific finger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The findings of males outnumbering females by a ratio of 7:1 in the study of Montandon C et al are different from our result. The most commonly involved finger was the ring finger (n=6) followed by the index finger in the present study which was similar to the findings of Montandon C et al and Jawalkar H et al13,14 The mean duration of the symptoms is relatively long and variable before establishing the diagnosis of the glomus tumor probably because of the rarity of the tumor and lack of awareness from the clinicians. The mean duration of symptoms was 1.8 years in the present study which is similar to the findings of Saaiq M (18 months), Santoshi JA et al (3.8 years), and Jawalkar H et al (3.25 years).The color change in the nail was noted in the 2 cases only and no case had nail deformity at the time of presentation.…”
supporting
confidence: 90%
“…The findings of males outnumbering females by a ratio of 7:1 in the study of Montandon C et al are different from our result. The most commonly involved finger was the ring finger (n=6) followed by the index finger in the present study which was similar to the findings of Montandon C et al and Jawalkar H et al13,14 The mean duration of the symptoms is relatively long and variable before establishing the diagnosis of the glomus tumor probably because of the rarity of the tumor and lack of awareness from the clinicians. The mean duration of symptoms was 1.8 years in the present study which is similar to the findings of Saaiq M (18 months), Santoshi JA et al (3.8 years), and Jawalkar H et al (3.25 years).The color change in the nail was noted in the 2 cases only and no case had nail deformity at the time of presentation.…”
supporting
confidence: 90%
“…The diversity of glomus bodies in the human body means that tumors involving these structures can be found in many different sites. They have been reported in subungual regions, 7,8 and, more rarely, in other areas such as the liver, stomach, lungs, bones, joints, genital organs, central nervous system, and blood vessels. Carotid glomus tumors arise from paraganglion cells and develop in the adventitial layer of the vessel, at the bifurcation of the common carotid artery, in a posteromedial position.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler ultrasonography was positive in five cases showing a hypoechoic nodule with internal vascularity [19]. Magnetic resonance imaging was positive in all of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging was positive in all of the cases. It showed solid nodule, hypointense on T1- and hyperintense on T2-weighted image, with homogeneous contrast enhancement [19]. In a study by Trehan et al, MRI findings in 36 of the 46 patients who had pathologically confirmed hand glomus tumor were analysed.…”
Section: Discussionmentioning
confidence: 99%